2022
DOI: 10.1186/s12959-022-00414-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and clinical impact of major bleeding in hospitalized patients with COVID-19: a sub-analysis of the CLOT-COVID Study

Abstract: Background The coronavirus disease 2019 (COVID-19) causes extensive coagulopathy and a potential benefit of anticoagulation therapy has been documented for prevention of thromboembolic events. Bleeding events has also been reported as a notable complication; whereas, the incidence, risks, and clinical impact of bleeding remain unclear. Method The CLOT-COVID Study was a nationwide, retrospective, multicenter cohort study on consecutive hospitalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Although the role of a percussive device in the development of an RSH in this patient is uncertain, we feel it may have been at least a contributing factor. The possible risk of using such devices in patients with severe COVID-19 who are on anticoagulant therapy must be considered, as these patients have a high incidence of major bleeding [10], including spontaneous RSHs [4]. Indeed, the retrospective study by Emekli et al [3] of 9,876 hospitalized COVID-19 patients receiving anticoagulants identified 0.12% (12 patients) who developed RSHs, with anticoagulant use ranging from 4 to 10.75 days at therapeutic doses.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of a percussive device in the development of an RSH in this patient is uncertain, we feel it may have been at least a contributing factor. The possible risk of using such devices in patients with severe COVID-19 who are on anticoagulant therapy must be considered, as these patients have a high incidence of major bleeding [10], including spontaneous RSHs [4]. Indeed, the retrospective study by Emekli et al [3] of 9,876 hospitalized COVID-19 patients receiving anticoagulants identified 0.12% (12 patients) who developed RSHs, with anticoagulant use ranging from 4 to 10.75 days at therapeutic doses.…”
Section: Discussionmentioning
confidence: 99%
“… 4 ) Independent factors for major bleeding have been reported, including a history of major bleeding, severe COVID-19 infection, and use of anticoagulants. 12 ) Anticoagulation in these patient groups requires more caution. When the risk of bleeding decreases, it may be necessary to consider the resumption of appropriate anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 9 ) Thrombus development was associated with COVID-19 severity, and bleeding risk was related to COVID-19 severity and anticoagulation but not with age. 10 12 )…”
Section: Introductionmentioning
confidence: 99%
“…Other clinical outcomes aside from thrombosis could also be important when considering anticoagulation therapy. A previous study showed that the incidence of major bleeding was not uncommon, especially in patients with severe COVID-19, and independent risk factors for major bleeding included history of major bleeding, COVID-19 severity, and anticoagulant use, which could be associated with poor clinical outcomes, including higher mortality 61) . Another previous study reported several independent risk factors for mortality in hospitalized patients with COVID-19, such as age >70 years, high D-dimer values on admission, heart disease, active cancer, higher COVID-19 severity on admission, and development of major bleeding during hospitalization, which could facilitate appropriate risk stratification of COVID-19 patients 62) .…”
Section: L I N I C a L Ev I D E N C E S O F T H R O M B O S I S A N D...mentioning
confidence: 99%